Tailored peptide hydrogel-based three-dimensional system improves stem cell maintenance, therapeutic potential and differentiation - Li, Quan (Kansas State University, 2024)
Stem cells are a type of cells capable of self-renewal and differentiation and exist in both fetal and adult tissues. Stem cells can be totipotent, pluripotent and multipotent with decreasing differentiation potentials. Multipotent stem cells like hematopoietic stem cells have already been used to treat some diseases as they can give rise to blood cells, but application of other stem cells is still limited. Pluripotent stem cells, i.e. embryonic stem cells (ESCs) are isolated from early-stage embryos and are thus limited by donor scarcity. Thanks to the development of human induced pluripotent stem cells (hiPSCs), cell source is no longer an issue, but the maintenance of iPSC still poses challenges. Previously we developed a three-dimensional (3D) method that produces large amount of high quality hiPSCs, but the mechanism for 3D iPSC maintenance is still unexplored. Based on the previous established 3D hiPSC culture methods using peptide hydrogel PGmatrix, we found that the better proliferation performance compared to other hydrogel-based 3D culture system was due to ability of the hiPSCs to modify its surrounding environment. During growth in PGmatrix, the hydrogel strength changed. The mechanical cues can be sensed by hiPSC, leading to modulation of proliferation. The novel 3D method can help fulfill the need of high quality iPSCs for downstream applications like therapeutic treatments and differentiation. Liver hepatocytes, as an example, is in large demand not only for disease treatment but also for pharmaceutical development. However, hepatocytes derived from iPSCs are still functionally far from primary hepatocytes, there is a thus need to improve the differentiation method. Compared to differentiation in matrix-free non-adherent plate, the hepatocyte organoids obtained from PG-suspension had significantly higher expression of key hepatocytes genes, some gene expression and in vitro detoxification function were comparable to primary hepatocytes. Besides modeling and treating diseases with cells or organoids differentiated from iPSC, there are also therapies that use stem cells directly. Currently mesenchymal stem cells (MSCs) are preferred for therapeutics because these cells can release more growth factors and signaling molecules then iPSCs, but 2D-culture MSCs showed varied level of treatment effects mainly because they were not adapted to the in vivo niche. Studies showed that MSC therapeutic potential improved after adopting 3D conformation, but there’s yet a method that steady MSC 3D preparation and delivery for treatment. In therapeutic application, we encapsulated MSCs in PGmatrix overnight before treatment through injection. Compared to hyaluronic acid (HA) and Hystem hydrogel, PGmatrix preserved high cell viability, promoted pluripotency protein expression and improved skin wound healing at an early stage in mice. Together, these results demonstrated improvements in stem cell research through application of PG hydrogel 3D systems. By tailoring peptide hydrogel for different research fields, there may be more advancement in stem cell related applications.
Keywords: Biomaterial; Hydrogel; Stem cell; 3D